2020
DOI: 10.1515/humor-2019-0021
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between teachers’ humor and class climate: A study targeting primary and secondary school students

Abstract: This study investigated the relationship between types of humor (aggressive humor and affinity humor) of homeroom teachers, as recognized by their students, and five domains of class climate (mutual respect among the students, discipline, willingness, enjoyment, and resistance). The participants included a total of 500 students – 250 primary school students (fourth to sixth grade) and 250 secondary school students (seventh to ninth grade) in Japan. The students answered questions about their homeroom teacher’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…It was also demonstrated that the factor structures of these two types of teacher humor apply regardless of a students’ school-going age. Aggressive humor as identified by Tsukawaki et al. (2020) and Bieg and Dresel (2016) includes the similar elements of teasing and satirizing students.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…It was also demonstrated that the factor structures of these two types of teacher humor apply regardless of a students’ school-going age. Aggressive humor as identified by Tsukawaki et al. (2020) and Bieg and Dresel (2016) includes the similar elements of teasing and satirizing students.…”
Section: Introductionmentioning
confidence: 97%
“…It has been documented that some types of humor used by teachers in a classroom setting—such as humor related to the course content, humor directed at oneself, and humor not involving aggression against others—has social functions. These functions include the building of good relationships with students and creating a positive climate (e.g., Aylor & Oppliger, 2003; Claus et al., 2012; Sidelinger, 2014; Tsukawaki et al., 2020), in addition to educational functions, such as increasing the motivation for learning and promoting the understanding of class content (e.g., Bieg et al., 2017, 2019; Bieg & Dresel, 2018; Tsukawaki & Imura, 2020). Teachers’ adaptive humor is also thought to improve students’ mental health (Lei et al., 2010; Ziyaeemehr et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations